A study to compare the efficacy of intermittent versus continuous regimen of pantaprazole in the management of upper gastrointestinal bleed (non variceal) - Mahajan, Uday; Kapoor, Dhiraj; Rana, B. S.; Kumar, Pankaj; Kumar, Dinesh; Malakar, Sayan; Dass, Bhagwan; Patial, Abhimanyu; Singh, Guriqbal (International Journal of Research in Medical Sciences, 2018)
Background: UGI bleeding is defined as bleeding that occurs in the digestive tract proximal to the ligament of treitz. Intermittent dosage regimen IV bolus and high dose IV continuous infusion forms helps in achieving and maintaining this pH goal of more than 6 which forms optimal environment for peptic ulcer healing and clot stabilization to occur. Theoretically, high-dose IV continuous infusion should provide the most potent acid suppression. Aims and objective was to compare the efficacy of intermittent dose of pantoprazole given for 3 days i.e. 40mg intravenous twice a day versus continuous infusion dose of pantaprazole i.e. 80mg intravenous bolus followed by 8mg/hour for first 72hours in the treatment of UGI bleed. Methods: Patients of UGI bleed were randomly assigned to receive either continuous or intermittent regimen of pantaprazole as a part of management. Results: Among 118 patients of peptic ulcer disease, 7 patients had rebleed and 111 patients had no rebleed.3 patients among 59 patients who received continuous regimen and 4 patients among 59 patients who received intermittent regimen had rebleed with a total of 7 patients among 118 patients. Among 118 patients only 2 patients of the total had need for surgery for stabilization. Among 59 patients who received continuous regimen 2 patients needed surgery while none of the 59 patients who received intermittent regimen needed for surgery. Of the 118 patients 10 patients had mortality at the end of 30 day period. In both the regimes 5 patients died. Conclusions: The difference between Rockall score of the intermittent and continuous regimen group was statistically insignificant. The incidence of rebleed was 5.1 % for continuous and 6.7% for intermittent regimen which was statiscally insignificant. The incidence of mortality was similar 8.5%in both regimen.